Evaluation on Sustainability of Technological Dimension Biopore Absorption Hole Management for Soil Water Conservation in Semarang City - Elesvera Destry; Hartuti Purnaweni; Syafrudin Syafrudin (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
Biopore technology innovation is an easy and cheap technology that can be applied in any class of society. Biopore Absorption Hole (BAH) is a cylincric vertical hole with a relatively small diameter. Eventhough the diameter is not so big, it is still effective to absorb groundwater.The dimension of technology reflected how this BAH tecnology is applied to the Management of BAH within the society of Semarang City.In order to achieve maximum results, an evaluation toward the sustainability of the dimension of BAH Management technology in Semarang City needs to be performed.The objectives of this research are to:1) studying the status of technology dimension in maintaining BAH, 2) studying sensitive attributes having influence toward index value and the sustainability status of technology dimension in maintaining BAH, as well as 3) formulating the priorities for policies applicable to technology in maintaining BAH in Semarang.The research took place in three administrative villages (Srondol Wetan, Jatingaleh, and Bendan Ngisor) in the city of Semarang.Those three locations were chosen to represent upper, middle, and lower regions of Semarang as water absorption area.The analysis of status determining data and leveraging factor was conducted using RAP – biopore method, while the the making of policy priorities was performed by using Analitycal Hierarchy Process (AHP).Results suggest that the status of the sustainability of Semarang’s BAH Management technology dimension was on “less sustainable” status (25,01 – 50,00). The strategy of enhancing influential sensitive attributes to improve sustainability status was a great success in affecting the values and sustainability status. Keywords :Biopore, RAP-Fish Modification, Sensitive Attribute, AHP, BAH Management.